Systematic Risk and the Price Structure of Individual Equity Options - Duan, Jin-Chuan; Wei, Jason (Review of Financial Studies, 2009)
This study demonstrates the impact of systematic risk on the prices of individual equity options. The option prices are characterized by the level and slope of implied volatility curves, and the systematic risk is measured as the proportion of systematic variance in the total variance. Using daily option quotes on the S, and P 100 index and its 30 largest component stocks, we show that after controlling for the underlying asset's total risk, a higher amount of systematic risk leads to a higher level of implied volatility and a steeper slope of the implied volatility curve. Thus, systematic risk proportion can help differentiate the price structure across individual equity options.